Implementation of an Integrated Problem Based Learning Model in Generic Science Skills in Thermochemical Material - Happy Nina Nola Chrystine Sinamo; Marudut Sinaga (Universitas Negeri Medan, 2024)
This research aims to determine the effect of Prior Knowledge Evaluation, Student Worksheets on student learning outcomes using the Problem Based Learning Model Integrated Generic Science Skills on Thermochemical Material. This research was carried out at SMAN 2 Percut Sei Tuan in the 2022/2023 academic year, the research was designed using a dual paradigm with two independent variables, namely Prior Knowledge Evaluation and Student Worksheets and one dependent variable, namely Evaluation of Learning Outcomes. The population in this study was all class XI at SMAN 2 Percut Sei Tuan. The sample used class XI B as an experimental class taught with Prior Knowledge Evaluation, Student Worksheets and Evaluation of Learning Outcomes tools using the Generic Science Skills Integrated PBL Learning Model. Sampling was using purposive sampling technique. The instruments used in this research consisted of 25 Prior Knowledge Evaluation questions, 15 Student Worksheets questions and 28 Evaluation of Learning Outcomes in multiple choice form which had been developed by previous researchers. The results of this study that thereare significant influence between Prior Knowledge Evaluation and Student Worksheets on learning outcomes. There are differences in learning outcomes between students who have low Prior Knowledge Evaluation and high Prior Knowledge Evaluation.